Richard Jenkins: Being Danish. Paradoxes of Identity in Everyday Life. København: Museum Tusculanum Press 2011. 355 sider. ISBN 978- 87-635-2603-6. Pris: 350 kr. - Schwartz, Jonathan Matthew (Tidsskriftet Antropologi, 2011)
Intet resumé